2001
DOI: 10.1088/0957-0233/12/5/201
|View full text |Cite
|
Sign up to set email alerts
|

Laser Rayleigh scattering

Abstract: Rayleigh scattering is a powerful diagnostic tool for the study of gases and is particularly useful for aiding in the understanding of complex flow fields and combustion phenomena. Although the mechanism associated with the scattering, induced electric dipole radiation, is conceptually straightforward, the features of the scattering are complex because of the anisotropy of molecules, collective scattering from many molecules and inelastic scattering associated with rotational and vibrational transitions. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
243
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 475 publications
(248 citation statements)
references
References 55 publications
2
243
0
3
Order By: Relevance
“…Asymmetric molecules typically also have significant dipole moments, the effects of which are described by the ED model. The RS model only describes an aspect of molecules consisting of larger numbers of atoms, such as CH 4 or H 2 S, but because of TABLE II. The four kinetic models considered, the property of gas molecules which they represent, their parameters, which of the gases under investigation in this work they can be applied to, and references which contain the expressions used for the bulk viscosity and the other transport coefficients.…”
Section: Kinetic Models and Bulk Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…Asymmetric molecules typically also have significant dipole moments, the effects of which are described by the ED model. The RS model only describes an aspect of molecules consisting of larger numbers of atoms, such as CH 4 or H 2 S, but because of TABLE II. The four kinetic models considered, the property of gas molecules which they represent, their parameters, which of the gases under investigation in this work they can be applied to, and references which contain the expressions used for the bulk viscosity and the other transport coefficients.…”
Section: Kinetic Models and Bulk Viscositymentioning
confidence: 99%
“…Line shapes in spontaneous Rayleigh-Brillouin scattering ͑SRBS͒ have been predicted most succesfully [2][3][4] by the theoretical model developed by Boley et al 5 and Tenti et al 6 In this model, information regarding the Boltzmann collision integral is obtained from transport coefficients. Pan et al successfully extended the model of Boley et al 5 to predict coherent Rayleigh-Brillouin scattering ͑CRBS͒ and reported good agreement with experimental data on several monatomic and molecular gases.…”
Section: Introductionmentioning
confidence: 99%
“…sin(θ/2) , (2.1) where θ is the scattering angle defined relative to the laser propagation direction, λ is the laser wavelength in nanometres, T is the temperature in kelvin and P is the pressure in atmospheres [6]. The broadening of the Rayleigh line can be described using either sixth moment (Tenti, Pan) or seventh moment (Pan) models of the density fluctuation spectrum, derived from approximate solutions of the time-dependent Boltzmann equation [7,8].…”
Section: P(atm)λ(nm)mentioning
confidence: 99%
“…For standard air (298 K, 1 atm) at 532 nm, F = 1.049 [6], so the depolarization ratio is 0.014. The depolarization ratio for pure oxygen is 0.027, and for nitrogen it is 0. .…”
Section: P(atm)λ(nm)mentioning
confidence: 99%
“…Optical flow velocity measurements based on Rayleigh scattering are described for instance in [11][12][13][14][15][16][17]. An overview article exists from Miles, 2001 [18]. The flow velocity measurements are based on the optical Doppler effect, which causes a shift in the observed scattered light frequency due to the scattering at the moving fluid particles.…”
Section: Introductionmentioning
confidence: 99%